Penerapan Teknologi Smart Farming dalam Peningkatan Kelembagaan Sentra Produksi Tempe Pliken Kembaran Banyumas - Anri Kurniawan; Chamid Sutikno; Rochman Tri Handoko (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2025)
Pliken Village, located in Kembaran District, Banyumas Regency, is recognized as one of the largest tempe production centers in Indonesia. However, most production activities are still conducted using traditional methods, resulting in uncontrolled fermentation processes, inconsistent product quality, limited shelf life, and weak institutional management. This community service program aimed to enhance partner capacity through the implementation of smart farming and smart packaging technologies to strengthen the institutional structure of the Pliken Tempe Production Center. The program employed a participatory approach involving socialization, training, mentoring, and the application of Internet of Things (IoT)-based technology. Smart farming technology was applied to the fermentation chamber to automatically control temperature and humidity, while smart packaging was introduced to improve packaging quality and product identity. Program evaluation was conducted through field observation and pre-test and post-test assessments. The results indicated a significant increase in participants’ knowledge, with average scores rising from 56.3 to 84.7. The smart farming system successfully maintained fermentation temperature at 30–35°C and relative humidity at approximately 70%, resulting in more consistent tempe quality and extending product shelf life to approximately 10–12 days. In addition to technical improvements, the program strengthened institutional capacity through the implementation of simple business record-keeping, improvement of business legality, and enhanced managerial readiness of partners. The integration of smart farming, smart packaging, and institutional strengthening proved effective in improving the competitiveness and sustainability of tempe-based MSMEs and shows strong potential for replication in other tempe production centers with similar characteristics